Differential cross sections for electron-impact excitation of laser-excited$\less$sup$\greater$174$\less$/sup$\greater$Yb (…6s6p\hspace0.167em$\less$sup$\greater$3$\less$/sup$\greater$P$\less$sub$\greater$1$\less$/sub$\greater$) - Hein, Jeff; Kidwai, S.; Zetner, P. W.; Bostock, C.; Fursa, D. V.; Bray, I.; Sharma, Lalita; Srivastava, R.; Stauffer, A. (Journal of physics. B, Atomic, molecular and optical physics, 2011)
We have measured and calculated electron-impact excitation cross sections from the laser-excited Yb (…6s6p 3P1) level to the higher-lying Yb (…6s6p 1P1), (…6s5d 3D1, 2, 3) and (…6s7s 3S1) levels at 20 eV impact energy. Measurements were performed using a crossed-beam apparatus, with resonant laser radiation incident on the electron-atom interaction region, providing excited-state atomic targets. Calculations were performed in the relativistic convergent close-coupling (RCCC), convergent close-coupling (CCC), and relativistic distorted-wave (RDW) approximations. We present measured and calculated partial differential cross sections (), which relate to differential cross sections and electron-impact coherence parameters through the target state anisotropy introduced by the laser geometry. Using theoretical predictions of the h electron-impact coherence parameter, we present the differential cross section for the 3P1-3S1 excitation.
Published 16 December 2010
Gesehen am 04.10.2022